Healthcare information on YouTube: A systematic review - Madathil, Kapil Chalil; Rivera-Rodriguez, A Joy; Greenstein, Joel S; Gramopadhye, Anand K (Health informatics journal, 2015)
This article reviews the peer-reviewed literature addressing the healthcare information available on YouTube. Inclusion and exclusion criteria were determined, and the online databases PubMed and Web of Knowledge were searched using the search phrases: (1) YouTube* AND Health* and (2) YouTube* AND Healthcare*. In all, 18 articles were reviewed, with the results suggesting that (1) YouTube is increasingly being used as a platform for disseminating health information; (2) content and frame analysis were the primary techniques employed by researchers to analyze the characteristics of this information; (3) YouTube contains misleading information, primarily anecdotal, that contradicts the reference standards and the probability of a lay user finding such content is relatively high; (4) the retrieval of relevant videos is dependent on the search term used; and (5) videos from government organizations and professional associations contained trustworthy and high-quality information. YouTube is used as a medium for promoting unscientific therapies and drugs that are yet to be approved by the appropriate agencies and has the potential to change the beliefs of patients concerning controversial topics such as vaccinations. This review recognizes the need to design interventions to enable consumers to critically assimilate the information posted on YouTube with more authoritative information sources to make effective healthcare decisions.